The Innovation Region: An Attempt to Develop a Multivariate Analysis Model - Magdalena Zdun (Rozwój Regionalny i Polityka Regionalna)
The aim of the article is to present a novel model for the analysis of regional differentiation of innovation cultures. The research output of sociology in this area allows us to identify three strands of analysis: materialist, ideological and social. It also allows us to make inferences about cognitive reductionism associated with the adoption of a single selected perspective. This is also what the proposed model aims to counteract. It is intended to be a conceptual construct that enables a multivariate diagnosis of the regional diversification of innovation culture. At the same time, it highlights the fact, that a complete diagnosis of innovation requires an appropriate unit of analysis (region) and a related analytical category (culture). Linking together these concepts leads to constructing a model that allows us to determine the level of innovation in the modern world and its territorial differentiation. Investigating innovation in accordance with that model involves reaching the content of the different layers of culture and analysing the relationship between the different layers of innovation and the region. Each of the indicated layers can be diagnosed in a quantitative and qualitative way. This model will be built in three stages. In the first stage, a multivariate (i.e. including the material, ideological and social aspects) unit of analysis – region – will be constructed. In the second stage, a private diagnostic category, i.e. culture, will be matched to this unit. Stage three will bring the final construction of the model.